2017
DOI: 10.21767/1307-234x.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Fertilization and Egg De-adhesion Methods on Hatching and Survival of Clarias gariepinus (Burchell 1822) Fry

Abstract: Abstract:Egg adhesiveness has been a major problem affecting the hatchability of Clarias gariepinus. The removal of egg stickiness will improve aquaculture production through enhanced hatching rates. However, appropriate media for removal of adhesiveness in Catfish eggs is not yet well established. This study therefore, determine the optimum concentration and rinsing time of powdered milk (PM), Urea (UR) and Tannic acid (TA) for removal of adhesiveness of African catfish eggs and their effect on fertility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
3
4
0
3
Order By: Relevance
“…The highest percentage (32%) was obtained in treatment 2 exposed to papain for 30 secs and was significantly different (P<0.05) from control, and longer exposure times. This is in line with Kareem et al, (2017) who reported that every rinsing agent has a specific exposure time when they are most effective. The result obtained is also in line with other research that reported significant differences in adhesion between control and the use of rinsing agents.…”
Section: Discussionsupporting
confidence: 91%
“…The highest percentage (32%) was obtained in treatment 2 exposed to papain for 30 secs and was significantly different (P<0.05) from control, and longer exposure times. This is in line with Kareem et al, (2017) who reported that every rinsing agent has a specific exposure time when they are most effective. The result obtained is also in line with other research that reported significant differences in adhesion between control and the use of rinsing agents.…”
Section: Discussionsupporting
confidence: 91%
“…También se reportaron porcentajes de eclosión superiores al 80% en la lucioperca, Sander lucioperca, al eliminar la capa adherente de los huevos con ácido tánico a una concentración de 0.75 g L -1 y un tiempo de exposición entre uno y dos minutos (10). No obstante, porcentajes de eclosión menores al 5% fueron reportados en bagre africano, Clarias gariepinus, cuando emplearon ácido tánico a la misma concentración utilizada en este trabajo, pero con un tiempo de exposición de 0.5 min (12). Lo que sugiere que para un efecto eficiente del ácido tánico en el desgomado de los huevos de bagre puede ser necesario un mayor tiempo de exposición, como el que se hizo en este trabajo.…”
Section: Discussionunclassified
“…Para la eliminación de la capa adherente de los huevos en aquellas especies de peces que presentan dicha característica, se han empleado diversos métodos, desde tratamientos mecánicos como la agitación de los huevos para separarlos como en la lucioperca americana, Stizostedion vitreum (5), el empleo de productos naturales como arena, arcilla, leche en polvo y jugo de piña, para el desgomado de huevos de tenca, Tinca tinca (6); lucioperca, Sander lucioperca (7) y botete diana, Sphoeroides annulatus (8,9), hasta la aplicación de tratamientos químicos como urea, sulfito de sodio, enzimas proteolíticas y ácido tánico, en el desgomado de huevos de lucioperca, S. lucioperca (10) vaqueta, Labrus bergylta (11), bagre africano, Clarias gariepinus (12), trucha arcoiris, Oncorhynchus mykiss (13), tenca, T. tinca (14), lucioperca, S. lucioperca (15) y esperlano arcoiris, Osmerus mordax (16).…”
Section: Introductionunclassified
“…At high concentration, tannic caused the chorion to harden, thus decreasing the chorionase activity and the development of embryogenesis is disrupted (Kareem et al, 2017). High concentration of tannic acid gave a negative impact on the pikeperch larvae hatching has been reported by Zakes et al (2005).…”
Section: The Effect Of Different Doses and Immersion Time On The Fert...mentioning
confidence: 96%